Rethinking Contemporary Pesantren Law and Economic Independence: A Legal Economic Approach to Institutional Sustainability - Anas Alhifni; Biyati Ahwarumi; Radif Khotamir Rusli; Ramadhita; Firdaus Arifin; Naim Demirel (MILRev: Metro Islamic Law Review, 2026)
This study critically examines the relationship between Law No. 18 of 2019 concerning Pesantren and the realization of economic independence within Islamic boarding schools in Indonesia through the perspective of law and economics. Although the law formally recognizes pesantren as institutions of community empowerment, this article questions whether normative legal recognition is sufficient to create sustainable economic autonomy. The research employs a doctrinal legal method combined with an institutional economics approach, emphasizing incentive structures, transaction costs, institutional governance, and economic sustainability. Data were analyzed through statutory interpretation, conceptual analysis, and institutional evaluation of pesantren economic practices in contemporary Indonesia. The findings demonstrate a significant gap between normative legal expectations and practical implementation. Many pesantren continue to experience structural limitations in access to capital, managerial professionalism, market integration, and institutional competitiveness, resulting in continued dependence on state assistance and donor-based programs. The study further reveals that the effectiveness of pesantren law is strongly influenced by the design of legal-economic incentives, institutional differentiation between resource-rich and resource-poor pesantren, and the integration of pesantren enterprises into the broader Islamic financial ecosystem. This article argues that economic independence should not be understood as an automatic consequence of legal recognition, but rather as a dynamic and negotiated process involving the interaction of state regulation, market mechanisms, and religious authority. The study contributes to contemporary Islamic legal scholarship by offering an institutional economics framework for pesantren development and proposing policy recommendations focused on incentive-based regulation, tiered Sharia-compliant financing, and sustainable institutional capacity building for pesantren economic transformation.